2019
DOI: 10.1021/acs.biochem.8b01300
|View full text |Cite
|
Sign up to set email alerts
|

K-RasG12D Has a Potential Allosteric Small Molecule Binding Site

Abstract: KRAS is the most commonly mutated oncogene in human cancer, with particularly high mutation frequencies in pancreatic cancers, colorectal cancers, and lung cancers [Ostrem, J. M., and Shokat, K. M. (2016) Nat. Rev. Drug Discovery 15, 771–785]. The high prevalence of KRAS mutations and its essential role in many cancers make it a potentially attractive drug target; however, it has been difficult to create small molecule inhibitors of mutant K-Ras proteins. Here, we identified a putative small molecule binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…Through a combination of computational methods and with the validation of biochemical assays, the authors proposed a mechanism of action for KAL-21404358. The quinoline compound could interfere with the protein-protein interactions, binding and stabilizing K-Ras in its inactive GDP-bound state, then, it halts the nucleotide exchange process and the subsequent activation of Ras [ 137 ].…”
Section: Quinolines As Inhibitors Of Carcinogenic Pathwaysmentioning
confidence: 99%
“…Through a combination of computational methods and with the validation of biochemical assays, the authors proposed a mechanism of action for KAL-21404358. The quinoline compound could interfere with the protein-protein interactions, binding and stabilizing K-Ras in its inactive GDP-bound state, then, it halts the nucleotide exchange process and the subsequent activation of Ras [ 137 ].…”
Section: Quinolines As Inhibitors Of Carcinogenic Pathwaysmentioning
confidence: 99%
“…Molecules that are in bold, are shown in Fig. 4 and Supplementary Figure S 2 , PDB IDs containing those molecules are shown in bold as well Binding target/site Effect Compound type PDB ID Representative example Reference SI/II-pocket (α2-helix and β1-β3 sheet) in the PPI surface Inhibition of GEF, GAP, and effector interaction Small molecule 6GJ5- 6GJ8 S1-BI-2852 Kessler-2019 [ 56 ] GEF-mediated nucleotide exchange inhibition 4DSO, 4DST, 4DSU S2-Benzimidazole DCAI Mauer-2012 [ 55 ] Inhibition of RAS-SOS binding 4EPR, 4EPY, 4EPX, 4EPW, 4EPT, 4EPV S3–‘Compound-4’ Sun-2012 [ 57 ] Inhibition of effector interaction 5OCO, 5OCT, 5OCG, 6FA1 , 6FA2, 6FA3, 6FA4 S4-ABD-4 S5-ABD-7 Qevedo-2018 [ 60 ] 6GOD, 6GOE, 6GOF, 6GOG, 6GOM, 6GQT, 6GQW, 6GQX, 6GQY Ch-3 Cruz-Migoni-2019 [ 59 ] Switch-II pocket (S-IIp) Inhibition of GTP loading to RAS Covalent small molecule 5F2E S6-ARS-853 Patricelli-2016 [ 34 ] 5V9U ARS-1620 Janes-2018 [ 42 ] 6OIM S7-AMG-510 Canon-2019 [ 27 ] 6UT0 S8-MRTX849 Fell-2020 [ 28 ] P110 pocket on the allosteric lobe of KRAS Allosteric inhibition of effector interaction Small molecule KAL-21404358 Feng-2019 [ 67 ] Allosteric lobe of KRAS Competitive inhibition of GEF Antibody-like protein ...…”
Section: Different Approaches and Sites To Target Krasmentioning
confidence: 99%
“…NMR results showed that upon binding of KAL-21404358, an early compound hit, Switch-I (Asp-33, Ser-39), and Switch-II (Leu-56, Gly-60, Met-67, Thr-74 and Gly-75) undergo conformational changes, suggesting an allosteric effect on KRAS-G12D. This resulted in inhibition of RAS-Raf interaction, and weak depletion of phosphorylated Akt, and ERK within treated cell lines [ 67 ]. These examples show that while selectively targeting non-G12C mutants of KRAS is complicated and requires less-straightforward strategies, it is possible to achieve, by taking advantage of the small structural changes that are caused by the mutated residue.…”
Section: Different Approaches and Sites To Target Krasmentioning
confidence: 99%
“…When discussing other K-RAS mutations such as mutation G12D, the aspartate side group was described as a difficult target [21]. Nevertheless, Feng et al have recently reported that K-Ras G12D has also a potential allosteric small molecule binding site [22]. Their work showed that one compound termed K-RAS allosteric ligand KAL-21404358, when bound to K-RAS G12D , impaired its interaction with B-RAF disrupting the RAF-MEK-ERK and PI3K-AKT signalling pathways [22].…”
Section: K-rasmentioning
confidence: 99%